Differentiated Linguistic Strategies of Bilingual Professionals on the U.S.-Mexico Border. Issue 1 (2nd January 2017) - Ramos, Diana Carolina; Sayer, Peter
Abstract : The authors present three distinct cases of English-Spanish bilinguals on the U.S.-Mexico border to illustrate how legitimate and authentic language use functions as forms of symbolic capital (P. Bourdieu, 1991 ). Language practices in the occupational domain exemplify how varieties of English and Spanish come into contact, are negotiated, and strategically utilized to situate oneself in a position of power within a linguistic market. The authors argue that because bilinguals have access to different forms of linguistic capital, in a highly bilingual context such as the U.S.-Mexico border, they develop differentiated strategies for employing language resources. The three strategies identified are avoidance, distribution, and engagement. Employing English-Spanish bilingualism through these differentiated strategies, participants exploit or compensate for their particular linguistic repertoire to meet the multilingual demands and language expectations of their workplace and, in doing so, reveal how languages are used in occupational settings as commodities with exchange value that can be transferred to other forms of capital. The authors suggest that the translanguaging practices (O. Garcia & L. Wei, 2014 ) observed serve in efforts to obtain symbolic capital in Laredo's linguistic market.